Modeling approach for the air convective drying of leafy materials - Orphanides, Antia; Fantousi, Antrea; Goulas, Vlasios; Gekas, Vassilis (My University, 2015)
Mathematical modeling in applied sciences could include predictive approaches in various unit operations of Chemical Engineering and/or Food Engineering. In air convective drying two key factors influence quantitatively and qualitatively the process and the processed material; temperature and air velocity. Although during the drying unit operation a severe shrinkage of leafy material occurs, no explicit account of this fact is taken in herb plant drying modeling. Even more rare, not to say un-existed, are applications of the true driving force, that is the thermodynamic driving force, according to the opinion of the authors. In this work both aspects have been considered and explicitly applied in the modeling of drying of a common herb plant, Mentha viridis, used as a model aromatic herb plant material. Furthermore, the study of synergistic or inhibitory effects between the influencing factors is presented. Application of the three before-mentioned aspects leads to interesting findings which are thoroughly discussed in the present paper.
Keywords: Drying; Modeling; Multifactorial analysis; Shrinkage; Water activity